Influence Factors of Visitor Compliance with The Implementation of Regional Regulation Policy Concerning Non-Smoking Areas at Blud of Subulussalam Regional General Hospital - Suharto, Teguh; Tarigan, Andini Mentari; Yuniati, Yuniati; Sulisna, Aida; Sukmayanti, Indah (Hasanuddin Medan, 2024)
Background: Cigarettes are a major cause of avoidable deaths in society. A non-smoking area is a designated space that explicitly prohibits the manufacturing, sale, advertising, promotion, and/or use of cigarettes. The Subulussalam City Government has implemented Subulussalam Mayor Regulation Number 52 of 2016, which prohibits smoking in designated areas. The purpose of this study is to identify the factors that impact visitor compliance with the implementation of Regional Regulation Policy Number 52 of 2016, which pertains to non-smoking areas in Subulussalam City Hospital's BLUD. The study employed an analytical survey methodology, utilizing a cross-sectional approach. We selected a subset of 86 individuals using the incidental sampling approach from the overall population of 636 individuals. The data analysis included univariate, bivariate, and multivariate analysis techniques, together with logistic regression test statistics. Outcome: The logistic regression analysis revealed significant findings for the variable’s knowledge (p-value = 0.000), attitude (p-value =.009), and the role of health personnel (p-value =.001). Conclusion: The knowledge, attitudes, and duties of health workers influence the implementation of Regional Regulation Number 52 of 2016, which pertains to non-smoking areas. We anticipate that the hospital will enhance visitor awareness by disseminating information through healthcare professionals and using posters, banners, and other informational media. This will help visitors understand the potential hazards to the hospital's surroundings and adhere to the hospital's designated no-smoking zone.